Abiraterone acetate plus prednisone in patients with newly diagnosed high-risk metastatic castration-sensitive prostate cancer (LATITUDE): final overall survival analysis of a randomised, double-blind, phase 3 trial. Issue 5 (May 2019) - Fizazi, Karim; Tran, NamPhuong; Fein, Luis; Matsubara, Nobuaki; Rodriguez-Antolin, Alfredo; Alekseev, Boris Y; Özgüroğlu, Mustafa; Ye, Dingwei; Feyerabend, Susan; Protheroe, Andrew; Sulur, Giri; Luna, Yesenia; et al.
Summary: Background: In the interim analyses of the LATITUDE study, the addition of abiraterone acetate plus prednisone to androgen deprivation therapy (ADT) led to a significant improvement in overall survival and radiographic progression-free survival compared with placebos plus ADT in men with newly diagnosed high-risk metastatic castration-sensitive prostate cancer (mCSPC). Here, we present long-term survival outcomes and safety of abiraterone acetate plus prednisone and ADT from the final analysis of the LATITUDE study. Methods: This is a multicentre, randomised, double-blind, phase 3 trial done at 235 sites in 34 countries. Eligible patients (men aged ≥18 years) had newly diagnosed, histologically or cytologically confirmed prostate cancer with metastases, Eastern Cooperative Oncology Group (ECOG) performance status of 0–2, and at least two of the three high-risk prognostic factors (Gleason score of ≥8, presence of three or more lesions on bone scan, or presence of measurable visceral metastasis except lymph node metastasis). Patients were randomly assigned (1:1) to receive abiraterone acetate (1000 mg) once daily orally plus prednisone (5 mg) once daily orally and ADT (abiraterone acetate plus prednisone group) or matching placebos plus ADT (placebo group); each treatment cycle was 28 days. Randomisation was done by a centralised interactive web response system in a country-by-country scheme using permuted block randomisation, stratified by presence of visceral disease and ECOG performance status. The coprimary endpoint of overall survival was assessed in the intention-to-treat population. This study is registered atClinicalTrials.gov, numberNCT01715285 and is complete. Findings: Between Feb 12, 2013, and Dec 11, 2014, 1209 patients were screened, of whom ten were ineligible because of study site violations. 1199 patients were randomly assigned to either the abiraterone acetate plus prednisone group (n=597) or placebo group (n=602). After the results of the first interim analysis (cutoff date Oct 31, 2016), the study was unmasked to patients and investigators, and patients in the placebo group were allowed to cross over to receive abiraterone acetate and prednisone plus ADT treatment as per a protocol amendment (Feb 15, 2017) in an open-label extension phase of the study (up to 18 months from the protocol amendment). This final analysis (data cutoff Aug 15, 2018) was done after a median follow-up of 51·8 months (IQR 47·2–57·0) and 618 deaths (275 [46%] of 597 in the abiraterone acetate plus prednisone group and 343 [57%] of 602 in the placebo group). Overall survival was significantly longer in the abiraterone acetate plus prednisone group (median 53·3 months [95% CI 48·2–not reached]) than in the placebo group (36·5 months [33·5–40·0]), with a hazard ratio of 0·66 (95% CI 0·56–0·78; p<0·0001). The most common grade 3–4 adverse events were hypertension (125 [21%] in the abiraterone acetate plus prednisone group vs 60 [10%] in the placebo group vs three [4%] in the 72 patients who crossed over from placebo to abiraterone acetate plus prednisone) and hypokalaemia (70 [12%] vs ten [2%] vs two [3%]). Serious adverse events of any grade occurred in 192 (32%) of 597 patients in the abiraterone acetate plus prednisone group, 151 (25%) of 602 in the placebo group, and four (6%) of 72 in the crossover group. The most common treatment-related serious adverse event was hypokalaemia (four [1%] patients in the abiraterone acetate plus prednisone group and none in the other groups). Treatment-related deaths occurred in three (<1%) patients each in the abiraterone acetate plus prednisone group (gastric ulcer perforation, sudden death, and cerebrovascular accident) and the placebo group (sudden death, cerebrovascular accident, and pneumonia), with none in the crossover group. Interpretation: The combination of abiraterone acetate plus prednisone with ADT was associated with significantly longer overall survival than placebos plus ADT in men with newly diagnosed high-risk mCSPC and had a manageable safety profile. These findings support the use of abiraterone acetate plus prednisone as a standard of care in patients with high-risk mCSPC. Funding: Janssen Research & Development.